Inelastic longitudinal electron scattering C2 form factors in 48Ca nucleus by using sigma meson as a residual interaction. - Majeed, Firas; Mashaan, Sadeq (Iraqi Journal of Science, 2023)
Inelastic longitudinal electron scattering C2 form factor in 48Ca has been utilizedto study the effects of fitting parameters on the sigma meson exchange typepotentials as a residual interaction. By coupling the core particles with model spaceparticle, where the latter used as an active part of residual interaction in the so calledcore polarization process, it is included as a correction with first order perturbationtheory to the main calculation of model space, and the excitation energy has beencarried out with ( ). A model space wave vectors are generated in full fp shellmodel with FPD6 as effective interaction with mixing configuration technique andharmonic oscillator as a single particle wave function. Theoretical results areconsisted with experimental data.